THE POSITION OF CHILD PROTECTION FROM THE PERSPECTIVE OF ISLAMIC LAW AND ITS PRACTICE IN MUSLIM FAMILIES - Nasywa Nabilah Nugroho; Faisar Ananda (Journal Analytica Islamica, 2026)
This study examines child protection from the perspective of Islamic law by focusing on the position of children as a trust (amanah), the legal foundations of child protection, and the practice of child protection within Muslim families. The study is motivated by the continuing occurrence of child rights violations such as neglect, violence, custody disputes, and the failure to provide post-divorce child support, which indicate that child protection in Muslim family life has not been fully implemented. This research employs normative legal research using conceptual, library, and Islamic juridical approaches. Data were collected from the Qur’an, Hadith, classical Islamic legal texts, scholarly journals, and contemporary Islamic legal literature, which were analyzed using descriptive qualitative methods. The findings reveal that Islamic law positions children as a trust that must be protected through the fulfillment of their rights to life, education, care, financial support, and protection from violence and neglect. Child protection in Islam is fundamentally based on the principles of maqāṣid al-syarī‘ah, particularly hifẓ al-nafs and hifẓ al-nasl, which aim to preserve human life and lineage. The practice of child protection in Muslim families is implemented through hadhanah (custody), financial support, moral and educational development, and post-divorce child protection by prioritizing the best interests of the child. However, its implementation still faces various obstacles, including low legal awareness, family conflicts, weak enforcement of court decisions, and social changes in modern society. Therefore, strengthening the understanding of Islamic law and enhancing the responsibility of families and the social environment are necessary to achieve optimal child protection in Muslim families